Weighting Terms and Procedures Against Citizens In Regaining Indonesian Citizenship - Supriyadi Arief (Badan Pembinaan Hukum Nasional, 2020)
The reciprocal relationship between the state and citizens is seen in the granting of citizenship status and obedience to the law by citizens. Citizenship status is important in determining this relationship. The problem in this study is what are the implications of the release of citizenship status in Indonesia and what are the ideal terms and procedures for regaining Indonesian citizenship This research is a normative study using a statutory approach, case approach and conceptual approach. The loss of citizenship status has implications for not fulfilling one's basic rights that can be granted by the state. Therefore, it should be subject to weighting conditions and procedures by adding provisional length of stay of 10-15 years, add 'lost citizenship' note to the police record and to the residence permit, increase Citizenship money, do social work for a certain time, announce the action in media, and temporarily suspend the application for citizenship